The Effects of Digitalization on Journalism: Changes and Transformations in Turkish Sports Journalism - Özgür Yılmaz (İletişim Kuram ve Araştırma Dergisi, 2025)
This study explores the transformative impact of digitalisation on sports journalism, with a specific focus on Turkish media. Historically, sports journalism evolved through traditional platforms such as newspapers, radio, and television, each shaping how sports were consumed and perceived. The advent of digital platforms has revolutionized this landscape, offering interactive and audience-centered experiences while challenging conventional norms and ethics. In Türkiye, digital platforms like YouTube and social media have become essential outlets for sports content, integrating real-time updates, fan-driven narratives, and personalized consumption. Text mining and content analysis were employed to examine the practices of prominent Turkish sports journalists and their interactions with audiences. The findings reveal that digitalisation has enhanced accessibility and engagement but also has amplified issues such as sensationalism, misinformation, and a narrow focus on football. The study highlights the hybrid nature of Turkish sports journalism, where traditional practices coexist with digital innovations. While digitalisation presents opportunities for inclusiveness and innovation, it also necessitates addressing persistent ethical and structural challenges. This research contributes to understanding the evolving dynamics of sports journalism in the digital age, emphasizing the need for a balance between technological advancements and professional integrity.